Kosmologi Waktu Umat Hindu: Mengapa Upacara Kuningan Harus Selesai Sebelum Tengah Hari? Perspektif Teo-Astronomi Hindu - Gupta, Gede Endy Kumara (Sphatika: Jurnal Teologi, 2026)
This study is positioned within the discipline of Hindu studies, with particular emphasis on the cosmology of time and the temporal organization of ritual practice in the Balinese Hindu tradition. It aims to explain the meaning of the restriction that the Kuningan holy day ritual must be completed before midday by situating it within the cosmological framework of the Sun’s movement. The problem arises from the fact that this prescription is generally understood as a normative rule based on the Sundarigama manuscript, without being thoroughly elaborated through a Hindu astronomical-theological framework. This study employs a qualitative approach through library research, applying Vedic hermeneutics to interpret the Sundarigama text and to relate it to the concepts of Jyotiṣa and the daily analogy of Dakṣiṇāyana-Uttarāyaṇa. The findings indicate that the period from midnight to midday can be analogized as a daily phase of Dakṣiṇāyana, a “descending” cosmic current that enables the presence of the Dewatas and Pitara in the human world. Conversely, the period from midday to midnight is analogized as a daily phase of Uttarāyaṇa, a cosmic current moving back toward the divine realm. For this reason, the Kuningan ritual must be completed before midday, since after that moment the cosmic flow is understood to be returning to svarga. This analysis confirms that the temporal restriction of Kuningan constitutes a consistent expression of Hindu cosmology of time, in which the movement of the Sun is conceived as a dynamic structure mediating the relationship between the human world and the divine realm.